Utilization of Shrimp Waste (Litopenaeus vannamei) as Powdered Broth: Effects of Roasting Duration on Protein Content, Color Changes, and FTIR - DIAH EKA MAULINA; Nurwati; Muhamad Hasdar (Bantara Journal of Animal Science, 2024)
Shrimp waste, such as shells and heads, can still be utilized to create powdered broth commonly used as a flavor enhancer in food. This research is intriguing because shrimp waste can substitute for MSG (monosodium glutamate). This study aims to investigate the impact of the roasting process duration on the protein content and physical properties of powdered broth derived from shrimp heads and shells. The primary treatment in this study involves varying roasting times, divided into four groups: K1 (30 min), K2 (40 min), K3 (50 min), and K4 (60 min). The protein content aligns with the quality requirements for flavor enhancers. Additionally, the L* color value ranges from 65-12-71.33, the a* value ranges from 2.23-5.61, and the b* value ranges from 22.71-25.32. Due to the prolonged drying process, the peaks of amide A, amide B, amide I, amide II, and amide III shift. The opportunity to utilize shrimp waste in the form of shells and heads for powdered broth is wide open for commercialization.
Keywords: Food and Agricultural Sciences; Protein Hydrolysis and Bioactive Peptides; Aquatic life and conservation